Early and long‐term results of surgery for secondary mitral regurgitation with a damaged heart. Issue 10 (3rd July 2019) - Kitamura, Hideki; Kagase, Ai; Koyama, Yutaka; Tamaki, Mototsugu; Kawaguchi, Yasuhiko
Abstract: Background: Surgery for secondary mitral regurgitation is still controversial, especially when the left ventricle is damaged. The Mitra Clip has been shown to be safe and effective for certain patient groups but does not offer superior control of mitral regurgitation compared with the surgery. If performed safely, the surgery can provide greater benefits over the long‐term. The objective of this study was to retrospectively investigate the early and long‐term results of mitral valve surgery for secondary mitral valve regurgitation with a damaged, dilated left ventricle. Methods: Patients with ejection fraction <40% and left ventricular end‐diastolic/systolic diameter >50/40 mm who underwent mitral valve surgery for secondary mitral regurgitation were investigated retrospectively. Results: The mean age of the 80 identified cases was 65.7 years, and 63 patients were male. Preoperative echocardiograms showed a mean ejection fraction of 25.2% and mean left ventricular diameters in diastole/systole of 64.5/56.9 mm, respectively. Mitral valve replacement was performed in 39 cases, and mitral valve plasty in 41 cases. The most common concomitant procedures were coronary artery bypass grafting and tricuspid valve surgery (41.3% each). Mitral regurgitation improved significantly from 3.5 to 0.83, and no operative or in‐hospital deaths were encountered. Long‐term results showed actual 1‐, 3‐ and 5‐year survival rates of 93.1%, 80.0%, and 64.7%, respectively (mean follow‐up, 1264 days). Conclusions: Early results of this study were good and long‐term results were acceptable. Our results suggest that mitral valve surgery is feasible for secondary mitral valve regurgitation even in dilated, damaged hearts.